2014
DOI: 10.1155/2014/902174
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Multimodal Anesthesia Using Regional Techniques in the Aging Surgical Patient

Abstract: Background. Elderly patients have unique age-related comorbidities that may lead to an increase in postoperative complications involving neurological, pulmonary, cardiac, and endocrine systems. There has been an increase in the number of elderly patients undergoing surgery as this portion of the population is increasing in numbers. Despite advances in perioperative anesthesia and analgesia along with improved delivery systems, monotherapy with opioids continues to be the mainstay for treatment of postop pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 72 publications
0
36
0
Order By: Relevance
“…97 In addition, the incorporation of regional techniques, including PCA epidural 98 for elderly patients has been shown to improve postoperative pain control and decrease hospital stay. 99,100 Postoperative epidural analgesia is superior to parenteral narcotics at reducing the rate of pulmonary complications and the need for prolonged ventilation or reintubation. Because it improves postoperative lung function and blood oxygenation, 101 epidural anesthesia should always be considered in elderly patients undergoing thoracic, abdominal, or major vascular surgery.…”
Section: Postoperative Analgesiamentioning
confidence: 99%
“…97 In addition, the incorporation of regional techniques, including PCA epidural 98 for elderly patients has been shown to improve postoperative pain control and decrease hospital stay. 99,100 Postoperative epidural analgesia is superior to parenteral narcotics at reducing the rate of pulmonary complications and the need for prolonged ventilation or reintubation. Because it improves postoperative lung function and blood oxygenation, 101 epidural anesthesia should always be considered in elderly patients undergoing thoracic, abdominal, or major vascular surgery.…”
Section: Postoperative Analgesiamentioning
confidence: 99%
“…Managing postoperative pain for these patients is equally challenging. Many anesthesia professionals use a checklist in preparing a multimodal approach to pain control for the surgical patient that includes risk reduction strategies 4 . When using a multimodal approach for the elderly patient, the following are some of the questions the anesthesia professional would consider.…”
Section: Physiological Effects Of Agingmentioning
confidence: 99%
“…Inhalation anesthetics have a 7% increase in effect for patients older than 30 years, and this effect continues to increase by 7% with each additional 10 years of age 5 . Regional blocks have the ability to target the area needed for pain relief and have been shown to have a decreased need for narcotic or sedative rescue and result in shorter stays in the postanesthesia care unit (PACU) 4 …”
Section: Physiological Effects Of Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…[38][39][40][41] Given these and other benefits of regional and neuraxial techniques, the risk-to-benefit ratio should be discussed with the patient and the surgical team as the anesthetic plan is constructed. Various studies have demonstrated that regional and neuraxial techniques are associated with decreased opioid consumption perioperatively, decreased pulmonary complications, and improved respiratory mechanics.…”
Section: Regional and Neuraxial Techniquesmentioning
confidence: 99%